Blumgart's surgery of the liver, biliary tract, and pancreas - Jarnagin, William R. (Surgeon); Blumgart, L.H (Elsevier Saunders, 2012)
Comprehensive and complete, Blumgart's Surgery of the Liver, Pancreas and Biliary Tract - edited by Dr. William R. Jarnagin and a team of experts- delivers the comprehensive, cutting-edge guidance you need to achieve optimal outcomes in surgery of the liver, biliary tract, and pancreas. Edited by a panel of experts and featuring contributions by many leading authorities, this 2-volume reference brings you the latest information on pathology, diagnostics, surgery, and non-operative intervention all in one source. At www.expertconsult.com you can not only access the complete contents online, but also an abundance of detailed illustrations and step-by-step procedural video clips from the Memorial Sloan Kettering video library that show you how to perform key procedures step by step. Glean all essential, up-to-date, need-to-know information in one comprehensive reference that provides extensive coverage of pathology, diagnostics, surgery, and non-operative intervention as well as hepatobiliary and pancreatic surgery. Deepen your understanding of surgical anatomy to help with diagnosis, surgical operation, interventional radiology, and endoscopy